* Forskydninger i repræsentation: Unormaliserede kroppe og disidentifikationsstrategier på scenen - Klint Wandahl, Emma Sofie (Peripeti, 2018)
This article seeks to facilitate an understanding, of how representational strategies of bodies produced as abnormal can operate within performance contexts. Informed by José Esteban Muñoz’ theory on disidentification and Robert McRuers theory on compulsory able-bodiedness the paper examines how the play Anatomi uses and can be read through the concept of disidentificationas a mode of relocating the contingency of identification possibilities.The strategy of the play offers a critical awareness that enables the audience to see more subtle subversions in stereotyped representation and therefore ultimately creates a context for norm criticism.